PHYTOCHEMICAL PROFILING OF MEDICALLY SIGNIFICANT CRUDE EXTRACT USING GC-MS ANALYSIS - Rajadurai, Maruthamuthu; Maithili, V.; Arunazhagi, R.; Yogesh, V. (International Journal of Current Pharmaceutical Research, 2018)
Objective: The objective of this research is to identify the phytochemical constitutions present in Natural crude extract which obtained from Thumlappati district. Methods: Kidney stone is one of the most clinical disorder arising nowadays. They are existing due to the depletion of the urine and disproportionate execration of the components such as oxalate, phosphate, uric, cysteine, and struvite. Many alopathy medicine are not effectively curable in the case of kidney stone, consequently people are in need of traditional medicine system. Thus there is a great demand for research on potential inhibitor from natural products for dissolving kidney stone. In present work deals with an unknown crude extract collected from G. Thumlappati, Battalagundu Dindugal district Tamil Nadu. The crude extract of phytochemical are analyzed by using GCMS method. Results: Thus the sample has some bioactive compound to discharge the stone particles. So we subjected the crude extract sample to GC-MS process which reveals 210 compounds in 21 different peaks. Conclusion: This studies forms a basis for the biological characterization and importance of bioactive compounds were identified.